2018
DOI: 10.1038/s41586-018-0466-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of glutamine synthetase in angiogenesis beyond glutamine synthesis

Abstract: Glutamine synthetase, encoded by the gene GLUL, is an enzyme that converts glutamate and ammonia to glutamine. It is expressed by endothelial cells, but surprisingly shows negligible glutamine-synthesizing activity in these cells at physiological glutamine levels. Here we show in mice that genetic deletion of Glul in endothelial cells impairs vessel sprouting during vascular development, whereas pharmacological blockade of glutamine synthetase suppresses angiogenesis in ocular and inflammatory skin disease whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
114
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(120 citation statements)
references
References 44 publications
6
114
0
Order By: Relevance
“…An investigation conducted by Kerr and Olson (1970) observed the formation of granulomatous pannus in the medullary spaces of chickens inoculated experimentally or contact-infected with MS. The present study demonstrated that several proangiogenic factors were upregulated, including ECM1 (Mongiat et al, 2003), IL-8 (Bodolay et al, 2002), TGF-β2 (Elshabrawy et al, 2015), SAA (Connolly et al, 2016), MMP-9 (Burrage et al, 2006), NRP1 (Kong et al, 2010), GLUL (Eelen et al, 2018), and THBS2 (Park et al, 2004), while antiangiogenic factors, including RGCC (An et al, 2009), as well as TIMP3 (Chen et al, 2014), were downregulated at both the mRNA and protein levels. These findings suggest that MS-infected CSF may contribute to blood vessel growth, which is necessary for sustaining pannus formation and the arthritis process.…”
Section: Il-8mentioning
confidence: 53%
“…An investigation conducted by Kerr and Olson (1970) observed the formation of granulomatous pannus in the medullary spaces of chickens inoculated experimentally or contact-infected with MS. The present study demonstrated that several proangiogenic factors were upregulated, including ECM1 (Mongiat et al, 2003), IL-8 (Bodolay et al, 2002), TGF-β2 (Elshabrawy et al, 2015), SAA (Connolly et al, 2016), MMP-9 (Burrage et al, 2006), NRP1 (Kong et al, 2010), GLUL (Eelen et al, 2018), and THBS2 (Park et al, 2004), while antiangiogenic factors, including RGCC (An et al, 2009), as well as TIMP3 (Chen et al, 2014), were downregulated at both the mRNA and protein levels. These findings suggest that MS-infected CSF may contribute to blood vessel growth, which is necessary for sustaining pannus formation and the arthritis process.…”
Section: Il-8mentioning
confidence: 53%
“…GLS1 and GLS2 isoforms are differentially expressed in RECs; the latter is more concentrated in endothelial tip cells necessary to new blood vessel formation 7 . Glutamine synthetase (GS) ablation prevents normal development of retinal vasculature, further confirming the importance of glutamine to endothelial cell growth and development 8 . Previous studies have also reported that RECs express the glutamine transporter SLC1A5 9 .…”
mentioning
confidence: 89%
“…For a cancer to sustain macroscopic tumour development and promote metastasis, the formation of neovasculature is necessary for the supply of nutrients and oxygen. This process, known as angiogenesis, is tightly regulated by opposing factors; stimulating and inhibiting the receptors displayed on the surface of vascular endothelial cells (4,5,60,61). Although key molecular regulators of angiogenesis have been identified, such as VEGF and TSP-1, it is now widely accepted that regulation of angiogenesis is a highly complex process, heavily influenced by the tumour microenvironment, gaining influence from things such as tumour metabolism, immune infiltrate and cancer-associated fibroblasts (CAFs) (62).…”
Section: St6gal1 In the Hallmarks Of Cancermentioning
confidence: 99%